Comparıson Of Wıts Appraısal Wıth Palatal Plane/A-B Measurement - Mehmet Birol Özel; F. Erhan Özdiller (Galenos Yayinevi, 2004)
The aim of this study was to compare Wits Appraisal with Palatal Plane/A-B measurement which is also used to evaluate maxillomandibular sagittal relationship. 54 measurements have been made on 203 lateral cephalograms of untreated adults and z scores of these have been calculated in order to make them comparable. After subtraction of z scores of the combinations; four groups were established according to the differences between them. (-∞<Z<-1) was considered as group I; (-1<Z<0) as group II; (0<Z<1) as group III; (1<Z<∞) as group IV. After this; all measurements have been evaluated by Variance Analysis and Duncan Test. The interpretation of these differences have yielded the following results: 1) All the other maxillomandibular sagittal relationship measurements are in agrement with the classification when the PD/AB and Wits measurements are in harmony. 2) Incisor positions measured according to A-Pg plane has a tendency to give false results by the increasing sagittal discrepancy.